2f+4f+9=29

Simple and best practice solution for 2f+4f+9=29 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2f+4f+9=29 equation:


Simplifying
2f + 4f + 9 = 29

Reorder the terms:
9 + 2f + 4f = 29

Combine like terms: 2f + 4f = 6f
9 + 6f = 29

Solving
9 + 6f = 29

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 6f = 29 + -9

Combine like terms: 9 + -9 = 0
0 + 6f = 29 + -9
6f = 29 + -9

Combine like terms: 29 + -9 = 20
6f = 20

Divide each side by '6'.
f = 3.333333333

Simplifying
f = 3.333333333

See similar equations:

| 7g-4g+4=9 | | 2t+5t-4=26 | | 11(-20+1)-4(-20-1)=2(-20-2)+4(-20-2) | | 2z+3z+5=45 | | 8n-2n+6=36 | | 3k+2k-5=30 | | 7(x-15)=37 | | 10x^3+8x^2+6x=0 | | 2(1)-3(2)= | | 2k^2=6k-4 | | 2(1)-3(2)=-4 | | 3x^2+17-33=0 | | 3x^2+17-33=o | | 1311x+52=8 | | 6(3z-10)=36 | | 30x^2-1x-20=0 | | 17-i=0 | | 3x+1x-1=6x+1 | | -6(-3x+8)=168 | | 56=-2(21-19)+4(19-4) | | m^2-16m+55=0 | | 86=3x+5x-2 | | 6(8y-5)=72 | | 2m+6+5m+10=23 | | solvex^4+9x-7=0forx | | 8=2x-x+1 | | 10x^2+12-16=0 | | 5m-5+2m=2 | | 3x-8(-3-5x)=24 | | 3+x-2x=6 | | m^2=-23m-132 | | x+5(2*4x)-3=14 |

Equations solver categories